(untitled) (Amsterdam, 2002)
Institutional recognition of the importance of interpreting studies is vital. Interpreting staﬀ on short-term contracts rarely have the opportunity to defend and assert the needs of interpreting pedagogy and interpreting research in an academic context which has frequently, hitherto, hoveredbetween hostility andindiﬀerence in most of Europe. It is comforting to reﬂect that Italy might well be right out in the orefront in this ﬁeld.
Keywords: Biên phiên dịch,Translating and interpreting